2014
DOI: 10.1177/1090198114547818
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Engagement and Independence

Abstract: Older adults, persons aged 65 or older, are growing in number faster than any other age group both nationally and internationally. In 2011, there were 41.4 million older adults in the United States. This means that one in eight people was an older adult (Administration on Aging, 2012). Globally by 2015, it is expected there will be more people over age 65 than young people aged 15 and younger (United Nations Population Fund & HelpAge International, 2012). This transformative demographic shift presents numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recent years, populations are growing older in nearly all the countries of the world especially in China [ 19 ]. Ageing process could reflect some extent of socioeconomic development, for instance the health problems of the aging of population have been a great challenge to social development [ 20 , 21 ]. Many studies have indicated that the elderly as a group are the greatest adult users of the health care system due to poor health [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years, populations are growing older in nearly all the countries of the world especially in China [ 19 ]. Ageing process could reflect some extent of socioeconomic development, for instance the health problems of the aging of population have been a great challenge to social development [ 20 , 21 ]. Many studies have indicated that the elderly as a group are the greatest adult users of the health care system due to poor health [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous engagement in roles helps form a role identity that then becomes a key part of a person’s identity (Burke & Tully, 1977). Volunteering may alleviate loss of roles experienced during retirement by promoting civic engagement (L. A. Anderson & Prohaska, 2014).…”
mentioning
confidence: 99%
“…Volunteering may alleviate loss of roles experienced during retirement by promoting civic engagement (L. A. Anderson & Prohaska, 2014). Volunteering is defined as, "Time individuals give without pay to activities performed either through an organization or directly for others outside their own household" (International Labour Organization, 2011, p. 13) and supports societal economic and health benefits, including increases in longevity and standard of living (Shmotkin et al, 2003).Past evidence suggests that volunteering may play an important role in reducing age-related cognitive decline, especially after retirement (Rohwedder & Willis, 2010).…”
mentioning
confidence: 99%